A study on awareness level of quantity surveying profession among secondary school students/ Afiqah Iliyana Samsul Bahari - Samsul Bahari, Afiqah Iliyana (2020)
Various career choice can be selected by learners from secondary education when they further study for tertiary education however lawyers, engineers, architects, and accountants are the typical and famous career amid secondary school learners, parents and guardians. Many past research has proved that secondary school students are not familiar with quantity surveyor occupation. This research paper is aim to study the level of awareness of Quantity Surveying occupation among students from secondary school. The three main objectives of this research are to highlight the roles and responsibilities of the quantity surveyor in the construction industry, to identify the current level of awareness of this profession among secondary school students and to study the possibilities of methodology to promote quantity surveying profession. The research was carried out around the Southern region of Sarawak where Quantitative analysis was used to obtain data for this study findings. A sum of 335 questionnaires were handed out and 150 of them returned back the survey where the percentage of response are at 45%. Data are analysed by using SPSS software where descriptive analysis are used. From the findings, the researcher finds that respondents who are aware of this profession are slightly higher than those who are not. However, most of the respondents have either no knowledge or little knowledge of the roles and responsibilities of this profession. Majority of the students agreed that school and mass media do affect their choice.